Women Education During Crisis: How Do Cosmetic and Health Industries Educate Women for Covid-19 Resilience and Provide Basis for Mitigation Education? - Suryani, Adi; Soedarso, Soedarso; Harry Budiutomo Harmadi, Sonny; Rahmawati, Deti; Prasetyawati, Niken; Suarmini, Ni Wayan (LPPM Universitas PGRI Semarang, 2024)
COVID-19 virus has been putting many people's health in peril and causing social anxiety, insecurity, and mayhem. It has become a public enemy. Collaboration between all sectors and community involvement are required to control the spread and negative effects of COVID-19. The beauty industry has emerged as one of several crucial sectors in the fight against COVID-19 Because they can make hand sanitizers, cleansers, hand gel, and lotions in large quantities that can protect the community and encourage community to stay healthy. This research explores the roles played by some locally produced beauty products in Indonesia in empowering women and girls to protect themselves from COVID-19. The study uses qualitative research methods. It examines ten cosmetics companies and incorporates interpretative analysis and web content analysis. The study examines the data from the perspective of community education and humanities. According to the study, the beauty industries typically employ three major strategies to educate their female and young girl customers. The first educational strategy is promoting self-health protection to make wellness and health goods. The second approach involves teaching women new healthy routines, safe, healthy makeup practices, and strict mask wearing and health plan implementation. The third strategy involves taking part in social educational activities that support and promote social skills among women and girls, such as empathy, care, and support. The study shows that women education is not only the responsibility of educational institutions, but also the business or industries sectors.